Steeple - Allison, John, 1976- (Dark Horse Comics, 2020)
A supernatural tale of friendship, the devil, and moral gray areas. Two women with wildly different worldviews become unlikely friends as they navigate the supernatural happenings in a sleepy coastal parish--and soon find themselves forced to choose sides in the war between good and evil, facing demons, curses, and a miniature Rapture!